Author Correction: Pan-cancer subtyping in a 2D-map shows substructures that are driven by specific combinations of molecular characteristics. Issue 1 (December 2018) - Taskesen, Erdogan; Huisman, Sjoerd; Mahfouz, Ahmed; Krijthe, Jesse; de Ridder, Jeroen; van de Stolpe, Anja; van den Akker, Erik; Verhaegh, Wim; Reinders, Marcel
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper